Evaluating the Effectiveness of the Islamic-based Training of Alcohols Disadvantages on Reduce Alcohol Craving and Relapse in Individuals with a History of Alcohol Addiction in the Alcoholics Anonymous (AA) in Tehran, 1396 - Vahideh Nasr; Nafiseh Nasr; Zeinab Malakzadeh; Fatemeh Malekzadeh-Mobaraki; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Alcohol is one of the most commonly abused drugs in the world. Today, despite extensive studies, preservative treatments to prevent recurrence of alcohol addiction have not been successful. Religion, as one of the main pillars of a nation's culture, has a powerful potential in preventing mental disorders and could be effective to prevent relapsing into alcohol consumption. The purpose of the present study was to evaluate the effectiveness of the Islamic-based training of the harms of taking alcohol on reducing alcohol craving and relapse into alcohol consumption in individuals with a history of alcohol addiction in the Alcoholics Anonymous Association (AA) in Tehran, 1396. Methods: This study was quasi-experimental in nature and used a pre-test and post-test control group design. The statistical population was composed of all the members of Alcoholics Anonymous Association (AA) in Tehran. Thirty individuals were selected by available sampling method. They were randomly assigned to intervention and control groups. Data was collected using the craving questionnaire. The course was presented in six two-hour sessions of training in which the attitude of Islam to alcohol consumption and the relevant scientific findings were discussed. ANOVA was used to determine the effect of Islamic-based training of the harms of alcohols on reducing alcohol craving and relapse. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: The findings showed the effectiveness of this kind of training on reducing alcohol craving and relapse at a significant level (P<0.05) in individuals with a history of alcohol addiction. Conclusion: It seems that Islamic-based training of the harms of alcohol could be potentially considered as an appropriate option to decrease alcohol craving in individuals with a history of alcohol addiction. Therefore, considering the effectiveness and cost-effectiveness of this method and its importance, it is recommended that individuals, organizations and the media use this method. For downloading the full-text of this article please click here. Please cite this article as: Nasr V, Nasr N, Malakzadeh Z, Malekzadeh-Mobaraki F, Karamkhani M. Evaluating the Effectiveness of the Islamic-based Training of Alcohols Disadvantages on Reduce Alcohol Craving and Relapse in Individuals with a History of Alcohol Addiction in the Alcoholics Anonymous (AA) in Tehran, 1396. Journal of Pizhūhish dar dīn va salāmat. 2020;6(1):36-46. https://doi.org/10.22037/jrrh.v6i1.18829